Strategi Pengembangan Pantai Melasti sebagai Daya Tarik Wisata di Desa Ungasan, Kecamatan Kuta Selatan, Kabupaten Badung - I Putu Widhi Eka Julyantara; I Nyoman Sunarta (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
Melasti beach is a tourist attraction of the beach that is just starting to develop. Melasti Beach still in development in the governance by the village of Ungasan and yet the existence of a management system. Melasti beach is located in Ungasan, South Kuta, Badung Regency, has the potentialities are wonderful and interesting to develop. The assumption behind this is based on the chosen research topic